Comparison of Health status among married and unmarried girls of late adolescent age in an urban slum of Delhi - Gupta, Sujata; Taneja, Neha; Chellaiyan, Vinoth Gnana; Liaqathali, Fasna (Indian Journal of Community Health, 2019)
Background: Late adolescent girls are being forced into marriage and the burden of marital responsibilities, most notably partner’s sexual demands and childbearing and child-rearing, led to significant emotional distress and depression. Thus, early marriage for girls might have profound impact on their health status. Aims & Objectives: To study impact of early marriage on health status of married girls of late adolescent age and to compare them with unmarried girls of same age. Material & Methods: A comparison study was conducted among girls of late adolescent age in an urban slum of North East Delhi. One sixty study participants were included in each group. A pretested interview schedule was used for collecting details such as knowledge on reproductive health, physical parameters and anemic status. Chi square tests were used and odds ratio was calculated. Results: Majority of married girls, 102(63.8%) had middle school education while 93(58.1%) of unmarried girls had high school education. The mean (SD) age of marriage of married adolescent girls was 17(±) years while their husband age at time of marriage was 21.6(±) years. Levels of hemoglobin were low in both groups 87.5% in married girls and 98.75% in unmarried girls. Conclusion: Early marriage was found to have impact on menstruation, reproductive health and nutritional status of adolescent girls.